Peran Film Dokumenter Sebagai Alat Edukasi Terhadap Dampak Kebijakan Pembangunan yang Merusak Lingkungan - Agung Widodo; Iwan Koswara; Priyo Subekti (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted with the aim of analyzing how a documentary film can be used as an educational and advocacy tool for the community regarding the impact of development policies on environmental aspects. This study focuses on a documentary film entitled